Graphene-based antistatic coating and preparation method thereof

By uniformly dispersing modified nickel-iron waste slag, modified red mud and reduced graphene oxide in antistatic coatings, forming a uniform conductive network, the problem of poor conductivity stability of existing antistatic coatings is solved, and excellent antistatic properties and chemical stability are achieved.

CN118496740BActive Publication Date: 2025-03-28DACHUANGXIN MATERIALS TECHNOLOGY (SHANDONG) CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410731945.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-06
Publication Date
2025-03-28
Estimated Expiration
2044-06-06

AI Technical Summary

Technical Problem

Existing antistatic coatings have problems such as uneven conductivity network, poor conductivity stability, and expensive metal filler coatings, high density and easy oxidation.

Method used

Using graphene-based antistatic coatings, the modified nickel-iron waste slag, modified red mud and reduced graphene oxide are uniformly dispersed in the curing system of epoxy resin to form a uniform conductive network structure to ensure the conductive durability of the coating.

Benefits of technology

The uniformity of the conductive network and strong conductivity stability of the antistatic coating are achieved, ensuring the excellent antistatic properties of the coating, and at the same time enhancing the antibacterial and anticorrosion properties of the coating, improving the stability of the chemical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004880466500000071
    Figure BDA0004880466500000071
Patent Text Reader

Abstract

The present invention belongs to the technical field of antistatic coatings, and specifically relates to a kind of antistatic coating based on graphene and its preparation method. The antistatic coating based on graphene of the present invention, in parts by weight, is composed of the following raw materials: 95-98 parts of o-cresol epoxy resin, 14-17 parts of dicyclopentadiene phenol epoxy resin, 62-65 parts of linear bisphenol A novolac resin, 1.5-2 parts of γ-methacryloxypropyl trimethoxysilane, 0.4-0.6 parts of polyphenylene sulfide, 4-5 parts of cellulose acetate butyrate, 10-12 parts of modified nickel-iron waste residue, 7-8 parts of modified red mud and 0.5-0.7 parts of reduced graphene oxide. The antistatic coating based on graphene of the present invention, by uniformly dispersing modified nickel-iron waste residue, modified red mud and reduced graphene oxide in the curing system of epoxy resin to form a uniform conductive network structure, synergistic effect between the three, ensures the conductive durability of the antistatic coating.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of antistatic coatings, and specifically relates to a graphene-based antistatic coating and a preparation method thereof. Background Art

[0002] The use of antistatic coatings can conduct the charges on the surface of polymer materials and eliminate the accumulated charges, thus achieving a good antistatic effect.

[0003] Commonly used polymer synthetic materials, such as plastics, rubber, synthetic fibers, etc., have high resistivity. They are prone to accumulate static electricity on their surfaces due to friction and other effects during use. When the accumulated static electricity reaches a certain amount, it is very easy to cause a series of problems. For example, due to static electricity, the surface of the material is very easy to absorb dust. Due to static electricity, radio navigation and communication equipment malfunction. If the static electricity generated by friction is not discharged in time, it will accumulate to a certain extent and produce spark discharge, which can lead to major accidents such as explosions and fires in severe cases. Therefore, it is very important to prevent and timely guide the accumulation of static electricity on the surface of the material. The use of antistatic coatings can conveniently and effectively eliminate the accumulation of static electricity during the use of polymer materials, thereby effectively ensuring the use of polymer materials and eliminating safety hazards during the use of polymer materials.

[0004] According to the composition and conductive mechanism, antistatic coatings can be divided into two categories: structural type and additive type. Additive antistatic coatings have been widely studied and applied, but they have the disadvantages of uneven conductive network and poor conductive stability. Metal fillers are limited in use due to their high price, high density and easy oxidation. Summary of the invention

[0005] The purpose of the present invention is to provide an antistatic coating based on graphene. The antistatic coating based on graphene has the characteristics of uniform conductive network and strong conductive stability. The present invention also provides a preparation method thereof.

[0006] The graphene-based antistatic coating of the present invention is composed of the following raw materials, measured in parts by weight: 95-98 parts of o-cresol epoxy resin, 14-17 parts of dicyclopentadiene phenol epoxy resin, 62-65 parts of linear bisphenol A novolac resin, 1.5-2 parts of gamma-methacryloxypropyltrimethoxysilane, 0.4-0.6 parts of polyphenylene sulfide, 4-5 parts of cellulose acetate butyrate, 10-12 parts of modified nickel-iron waste residue, 7-8 parts of modified red mud and 0.5-0.7 parts of reduced graphene oxide.

[0007] in:

[0008] The preparation method of modified nickel-iron waste slag comprises the following steps: mixing the nickel-iron waste slag with a sodium hydroxide solution for stirring reaction, then naturally cooling to room temperature, centrifugally separating, washing with water to neutrality, and drying to obtain the modified nickel-iron waste slag.

[0009] in:

[0010] The mass ratio of the sodium hydroxide solution to the nickel-iron waste slag is 5.5:1; the concentration of the sodium hydroxide solution is 50%.

[0011] The stirring reaction temperature was 190°C, the stirring reaction time was 100 min, and the stirring speed was 1000 r / min.

[0012] The drying temperature is 50-55°C and the drying time is 8-10h.

[0013] Ferronickel slag is a solid waste in the smelting process of ferronickel. The chemical composition of ferronickel slag is as follows: SiO 2 55.42%, MgO 31.32%, CaO 1.07%, Al 2 O 3 5.17%, TFe 4.01%, Ni0.03%, Cr 2 O 3 0.74%, loss on ignition 2.24%.

[0014] The preparation method of modified red mud comprises the following steps: the red mud is dried at 120° C. for 12 hours and then calcined at 680° C. for 70-75 minutes to prepare modified red mud.

[0015] in:

[0016] In terms of mass percentage, the chemical composition of red mud is as follows: Al 2 O 3 17.23%, Fe 2 O 3 45.56%、SiO 2 18.29%, CaO 4.59%, Na 2 O 3.42%, TiO 2 5.47% Loss on ignition 5.44%.

[0017] The preparation method of reduced graphene oxide comprises the following steps: adding deionized water into graphene oxide for ultrasonic oscillation, dropping ammonia water to adjust the pH value of the system to 9, adding hydrazine hydrate under stirring conditions, heating to 90°C and reflux for 100 minutes, cooling to room temperature after the reaction is completed and filtering, then washing with deionized water and ethanol, and drying at 60°C for 22 hours to prepare reduced graphene oxide.

[0018] The mass volume ratio of deionized water to graphene oxide is 0.1:100, in g / mL.

[0019] The mass ratio of hydrazine hydrate to graphene oxide is 0.875:1.

[0020] The graphene-based antistatic coating of the present invention comprises o-cresol formaldehyde epoxy resin and dicyclopentadiene phenol epoxy resin, which are compounded and cross-linked with linear bisphenol A phenol-formaldehyde resin to generate a two-phase system of semi-interpenetrating network polymer, reduce the internal stress of the cured product, and improve the heat resistance of the antistatic coating. The dicyclopentadiene phenol epoxy resin is additionally added, and after the dicyclopentadiene phenol epoxy resin is cured, the water absorption rate of the prepared powder coating after use can be reduced, and the chemical resistance performance can be improved.

[0021] The graphene-based antistatic coating described in the present invention is additionally added with modified nickel-iron waste slag, modified red mud and reduced graphene oxide, and the three act synergistically to ensure that the prepared coating has excellent antistatic properties. Among them, the nickel-iron waste slag in the modified nickel-iron waste slag is stirred and reacted with the strong base sodium hydroxide, which reduces the silicon dioxide content in the nickel-iron waste slag and increases the content of magnesium oxide and ferric oxide in the nickel-iron waste slag, thereby making the modified nickel-iron waste slag have a higher conductivity. The red mud is subjected to low-temperature calcination treatment, which increases the specific surface area and crystallinity while minimizing the Fe contained therein. 2 O 3 The loss of the red mud by the Bayer process is achieved by using the high iron content in the red mud to achieve good conductivity. Reduced graphene oxide is a kind of carbon atom in the form of sp 2 The hexagonal two-dimensional planar film composed of hybrid orbitals has a stable lattice structure that makes the carbon atoms have excellent electrical conductivity, and the high surface area of ​​reduced graphene oxide makes it have a large contact surface with epoxy resin, and the prepared powder coating has good insulation, so that it also has certain antibacterial and anticorrosive properties. Therefore, the modified nickel-iron waste residue, modified red mud and reduced graphene oxide are compounded and used. While ensuring that the prepared coating has excellent antistatic properties, the coating itself still has good antibacterial and anticorrosive properties, and enhances the chemical stability of the coating. In addition, polyphenylene sulfide and cellulose acetate butyrate are added to the antistatic coating, wherein the addition of polyphenylene sulfide can improve the bonding between the powder coating and the substrate, and cellulose acetate butyrate acts as a leveling agent.

[0022] The preparation method of the graphene-based antistatic coating of the present invention comprises the following steps: o-cresol-formaldehyde epoxy resin, dicyclopentadiene phenol epoxy resin, linear bisphenol A phenol-formaldehyde resin, γ-methacryloxypropyltrimethoxysilane, polyphenylene sulfide, cellulose acetate butyrate, modified nickel-iron waste residue, modified red mud and reduced graphene oxide are stirred and mixed uniformly, then melt-extruded to obtain an extruded sheet, and finally ground and pulverized to prepare the graphene-based antistatic coating.

[0023] in:

[0024] The stirring and mixing temperature is 75-80°C, and the stirring and mixing time is 5-8 minutes.

[0025] The melt extrusion temperature is 154-157°C.

[0026] Grind and pulverize through a 350 mesh sieve.

[0027] Compared with the prior art, the present invention has the following beneficial effects:

[0028] (1) The graphene-based antistatic coating of the present invention forms a uniform conductive network structure by uniformly dispersing modified nickel-iron waste slag, modified red mud and reduced graphene oxide in a curing system of epoxy resin, and the three act synergistically to ensure the conductivity durability of the antistatic coating.

[0029] (2) The method for preparing the graphene-based antistatic coating of the present invention is simple to operate and easy to implement, and the stability of the antistatic performance of the prepared coating is ensured through the interaction between the raw materials. DETAILED DESCRIPTION

[0030] The present invention is further described below with reference to the embodiments.

[0031] Example 1

[0032] The graphene-based antistatic coating described in this embodiment 1 is composed of the following raw materials, in parts by weight: 97 parts of o-cresol epoxy resin, 16 parts of dicyclopentadiene phenol epoxy resin, 64 parts of linear bisphenol A phenolic resin, 1.7 parts of γ-methacryloxypropyltrimethoxysilane, 0.5 parts of polyphenylene sulfide, 4.5 parts of cellulose acetate butyrate, 11 parts of modified nickel-iron waste slag, 7.5 parts of modified red mud and 0.6 parts of reduced graphene oxide.

[0033] in:

[0034] The preparation method of modified nickel-iron waste slag comprises the following steps: mixing the nickel-iron waste slag with a sodium hydroxide solution for stirring reaction, then naturally cooling to room temperature, centrifugally separating, washing with water to neutrality, and drying to obtain the modified nickel-iron waste slag.

[0035] in:

[0036] The mass ratio of the sodium hydroxide solution to the nickel-iron waste slag is 5.5:1; the concentration of the sodium hydroxide solution is 50%.

[0037] The stirring reaction temperature was 190°C, the stirring reaction time was 100 min, and the stirring speed was 1000 r / min.

[0038] The drying temperature was 53°C and the drying time was 9 h.

[0039] The chemical composition of nickel-iron waste slag is as follows in terms of mass percentage: SiO 2 55.42%, MgO 31.32%, CaO1.07%, Al 2 O 3 5.17%, TFe 4.01%, Ni 0.03%, Cr 2 O 3 0.74%, loss on ignition 2.24%.

[0040] The preparation method of modified red mud comprises the following steps: the red mud is dried at 120° C. for 12 hours and then calcined at 680° C. for 70-75 minutes to prepare modified red mud.

[0041] in:

[0042] In terms of mass percentage, the chemical composition of red mud is as follows: Al 2 O 3 17.23%, Fe 2 O 3 45.56%、SiO 2 18.29%, CaO 4.59%, Na 2 O 3.42%, TiO 2 5.47% Loss on ignition 5.44%.

[0043] The preparation method of reduced graphene oxide comprises the following steps: adding deionized water into graphene oxide for ultrasonic oscillation, dropping ammonia water to adjust the pH value of the system to 9, adding hydrazine hydrate under stirring conditions, heating to 90°C and reflux for 100 minutes, cooling to room temperature after the reaction is completed and filtering, then washing with deionized water and ethanol, and drying at 60°C for 22 hours to prepare reduced graphene oxide.

[0044] The mass volume ratio of deionized water to graphene oxide is 0.1:100, in g / mL.

[0045] The mass ratio of hydrazine hydrate to graphene oxide is 0.875:1.

[0046] The preparation method of the graphene-based antistatic coating described in this embodiment 1 consists of the following steps: o-cresol epoxy resin, dicyclopentadiene phenol epoxy resin, linear bisphenol A phenolic resin, γ-methacryloxypropyltrimethoxysilane, polyphenylene sulfide, cellulose acetate butyrate, modified nickel-iron waste residue, modified red mud and reduced graphene oxide are stirred and mixed evenly, then melt-extruded to obtain an extruded sheet, and finally ground and pulverized to prepare the graphene-based antistatic coating.

[0047] in:

[0048] The stirring and mixing temperature was 77°C and the stirring and mixing time was 7 minutes.

[0049] The melt extrusion temperature was 155°C.

[0050] Grind and pulverize through a 350 mesh sieve.

[0051] Example 2

[0052] The graphene-based antistatic coating described in this Example 2 is composed of the following raw materials, in parts by weight: 95 parts of o-cresol epoxy resin, 17 parts of dicyclopentadiene phenol epoxy resin, 62 parts of linear bisphenol A phenolic resin, 1.5 parts of γ-methacryloxypropyltrimethoxysilane, 0.6 parts of polyphenylene sulfide, 5 parts of cellulose acetate butyrate, 10 parts of modified nickel-iron waste slag, 8 parts of modified red mud and 0.5 parts of reduced graphene oxide.

[0053] in:

[0054] The preparation method of modified nickel-iron waste slag comprises the following steps: mixing the nickel-iron waste slag with a sodium hydroxide solution for stirring reaction, then naturally cooling to room temperature, centrifugally separating, washing with water to neutrality, and drying to obtain the modified nickel-iron waste slag.

[0055] in:

[0056] The mass ratio of the sodium hydroxide solution to the nickel-iron waste slag is 5.5:1; the concentration of the sodium hydroxide solution is 50%.

[0057] The stirring reaction temperature was 190°C, the stirring reaction time was 100 min, and the stirring speed was 1000 r / min.

[0058] The drying temperature was 50°C and the drying time was 8 hours.

[0059] The chemical composition of nickel-iron waste slag is as follows in terms of mass percentage: SiO 2 55.42%, MgO 31.32%, CaO1.07%, Al 2 O 35.17%, TFe 4.01%, Ni 0.03%, Cr 2 O 3 0.74%, loss on ignition 2.24%.

[0060] The preparation method of modified red mud comprises the following steps: the red mud is dried at 120° C. for 12 hours and then calcined at 680° C. for 70-75 minutes to prepare modified red mud.

[0061] in:

[0062] In terms of mass percentage, the chemical composition of red mud is as follows: Al 2 O 3 17.23%, Fe 2 O 3 45.56%、SiO 2 18.29%, CaO 4.59%, Na 2 O 3.42%, TiO 2 5.47% Loss on ignition 5.44%.

[0063] The preparation method of reduced graphene oxide comprises the following steps: adding deionized water into graphene oxide for ultrasonic oscillation, dropping ammonia water to adjust the pH value of the system to 9, adding hydrazine hydrate under stirring conditions, heating to 90°C and reflux for 100 minutes, cooling to room temperature after the reaction is completed and filtering, then washing with deionized water and ethanol, and drying at 60°C for 22 hours to prepare reduced graphene oxide.

[0064] The mass volume ratio of deionized water to graphene oxide is 0.1:100, in g / mL.

[0065] The mass ratio of hydrazine hydrate to graphene oxide is 0.875:1.

[0066] The preparation method of the graphene-based antistatic coating described in this Example 2 consists of the following steps: o-cresol epoxy resin, dicyclopentadiene phenol epoxy resin, linear bisphenol A phenolic resin, γ-methacryloxypropyltrimethoxysilane, polyphenylene sulfide, cellulose acetate butyrate, modified nickel-iron waste residue, modified red mud and reduced graphene oxide are stirred and mixed evenly, then melt-extruded to obtain an extruded sheet, and finally ground and pulverized to prepare the graphene-based antistatic coating.

[0067] in:

[0068] The stirring and mixing temperature was 75°C and the stirring and mixing time was 5 minutes.

[0069] The melt extrusion temperature was 154°C.

[0070] Grind and pulverize through a 350 mesh sieve.

[0071] Example 3

[0072] The graphene-based antistatic coating described in this Example 3 is composed of the following raw materials, in parts by weight: 98 parts of o-cresol epoxy resin, 14 parts of dicyclopentadiene phenol epoxy resin, 65 parts of linear bisphenol A phenolic resin, 2 parts of γ-methacryloxypropyltrimethoxysilane, 0.4 parts of polyphenylene sulfide, 4 parts of cellulose acetate butyrate, 12 parts of modified nickel-iron waste slag, 7 parts of modified red mud and 0.7 parts of reduced graphene oxide.

[0073] in:

[0074] The preparation method of modified nickel-iron waste slag comprises the following steps: mixing the nickel-iron waste slag with a sodium hydroxide solution for stirring reaction, then naturally cooling to room temperature, centrifugally separating, washing with water to neutrality, and drying to obtain the modified nickel-iron waste slag.

[0075] in:

[0076] The mass ratio of the sodium hydroxide solution to the nickel-iron waste slag is 5.5:1; the concentration of the sodium hydroxide solution is 50%.

[0077] The stirring reaction temperature was 190°C, the stirring reaction time was 100 min, and the stirring speed was 1000 r / min.

[0078] The drying temperature was 55°C and the drying time was 10 h.

[0079] The chemical composition of nickel-iron waste slag is as follows in terms of mass percentage: SiO 2 55.42%, MgO 31.32%, CaO1.07%, Al 2 O 3 5.17%, TFe 4.01%, Ni 0.03%, Cr 2 O 3 0.74%, loss on ignition 2.24%.

[0080] The preparation method of modified red mud comprises the following steps: the red mud is dried at 120° C. for 12 hours and then calcined at 680° C. for 70-75 minutes to prepare modified red mud.

[0081] in:

[0082] In terms of mass percentage, the chemical composition of red mud is as follows: Al 2 O 3 17.23%, Fe 2 O 3 45.56%、SiO 2 18.29%, CaO 4.59%, Na2 O 3.42%, TiO 2 5.47% Loss on ignition 5.44%.

[0083] The preparation method of reduced graphene oxide comprises the following steps: adding deionized water into graphene oxide for ultrasonic oscillation, dropping ammonia water to adjust the pH value of the system to 9, adding hydrazine hydrate under stirring conditions, heating to 90°C and reflux for 100 minutes, cooling to room temperature after the reaction is completed and filtering, then washing with deionized water and ethanol, and drying at 60°C for 22 hours to prepare reduced graphene oxide.

[0084] The mass volume ratio of deionized water to graphene oxide is 0.1:100, in g / mL.

[0085] The mass ratio of hydrazine hydrate to graphene oxide is 0.875:1.

[0086] The preparation method of the graphene-based antistatic coating described in this Example 3 consists of the following steps: o-cresol epoxy resin, dicyclopentadiene phenol epoxy resin, linear bisphenol A phenolic resin, γ-methacryloxypropyltrimethoxysilane, polyphenylene sulfide, cellulose acetate butyrate, modified nickel-iron waste residue, modified red mud and reduced graphene oxide are stirred and mixed evenly, then melt-extruded to obtain an extruded sheet, and finally ground and pulverized to prepare the graphene-based antistatic coating.

[0087] in:

[0088] The stirring and mixing temperature was 80°C and the stirring and mixing time was 8 minutes.

[0089] The melt extrusion temperature was 157°C.

[0090] Grind and pulverize through a 350 mesh sieve.

[0091] Comparative Example 1

[0092] The preparation method of the graphene-based antistatic coating described in this comparative example 1 is the same as that in Example 1, and the only difference is that the raw material composition of the graphene-based antistatic coating described in this comparative example 1 is different. The graphene-based antistatic coating described in this comparative example 1 is composed of the following raw materials in parts by weight: 97 parts of o-cresol epoxy resin, 16 parts of dicyclopentadiene phenol epoxy resin, 64 parts of linear bisphenol A novolac resin, 1.7 parts of γ-methacryloxypropyltrimethoxysilane, 0.5 parts of polyphenylene sulfide, 4.5 parts of cellulose acetate butyrate, 7.5 parts of modified red mud, and 0.6 parts of reduced graphene oxide.

[0093] Comparative Example 2

[0094] The preparation method of the graphene-based antistatic coating described in this comparative example 2 is the same as that in Example 1, and the only difference is that the raw material composition of the graphene-based antistatic coating described in this comparative example 2 is different. The graphene-based antistatic coating described in this comparative example 2 is composed of the following raw materials in parts by weight: 97 parts of o-cresol epoxy resin, 16 parts of dicyclopentadiene phenol epoxy resin, 64 parts of linear bisphenol A novolac resin, 1.7 parts of γ-methacryloxypropyltrimethoxysilane, 0.5 parts of polyphenylene sulfide, 4.5 parts of cellulose acetate butyrate, 11 parts of modified nickel-iron waste residue, and 0.6 parts of reduced graphene oxide.

[0095] Comparative Example 3

[0096] The preparation method of the antistatic coating described in this comparative example 3 is the same as that in Example 1, and the only difference is that the raw material composition of the antistatic coating described in this comparative example 3 is different. The antistatic coating described in this comparative example 3 is composed of the following raw materials in parts by weight: 97 parts of o-cresol epoxy resin, 16 parts of dicyclopentadiene phenol epoxy resin, 64 parts of linear bisphenol A phenolic resin, 1.7 parts of γ-methacryloxypropyltrimethoxysilane, 0.5 parts of polyphenylene sulfide, 4.5 parts of cellulose acetate butyrate, 11 parts of modified nickel-iron waste residue and 7.5 parts of modified red mud.

[0097] The performance of the graphene-based antistatic coatings prepared in Examples 1-3 and Comparative Examples 1-3 was tested, and the results are shown in Table 1 below:

[0098] Table 1 Test results of antistatic coating performance prepared in Examples 1-3 and Comparative Examples 1-3

[0099]

Claims

1. A graphene-based antistatic coating, characterized in that: The invention is composed of the following raw materials in parts by weight: 95-98 parts of o-cresol epoxy resin, 14-17 parts of dicyclopentadiene phenol epoxy resin, 62-65 parts of linear bisphenol A phenolic resin, 1.5-2 parts of γ-methacryloxypropyltrimethoxysilane, 0.4-0.6 parts of polyphenylene sulfide, 4-5 parts of cellulose acetate butyrate, 10-12 parts of modified nickel-iron waste residue, 7-8 parts of modified red mud and 0.5-0.7 parts of reduced graphene oxide; in: The preparation method of modified nickel-iron waste residue comprises the following steps: mixing the nickel-iron waste residue with a sodium hydroxide solution for stirring reaction, then naturally cooling to room temperature, centrifugally separating, washing with water to neutrality, and drying to obtain the modified nickel-iron waste residue; The mass ratio of the sodium hydroxide solution to the nickel-iron waste slag is 5.5:1; the concentration of the sodium hydroxide solution is 50%; The stirring reaction temperature was 190°C, the stirring reaction time was 100 min, and the stirring speed was 1000 r / min; The drying temperature is 50-55°C and the drying time is 8-10h; The chemical composition of ferronickel waste slag in terms of mass percentage is as follows: SiO2 55.42%, MgO 31.32%, CaO 1.07%, Al2O3 5.17%, TFe 4.01%, Ni 0.03%, Cr2O3 0.74%, loss on ignition 2.24%; The preparation method of modified red mud comprises the following steps: drying the red mud at 120° C. for 12 hours and then calcining the red mud at 680° C. for 70-75 minutes to prepare modified red mud; In terms of mass percentage, the chemical composition of red mud is as follows: Al2O3 17.23%, Fe2O3 45.56%, SiO2 18.29%, CaO 4.59%, Na2O 3.42%, TiO2 5.47% Loss on ignition 5.44%; The preparation method of reduced graphene oxide comprises the following steps: adding deionized water to graphene oxide for ultrasonic oscillation, adding ammonia water dropwise to adjust the pH value of the system to 9, adding hydrazine hydrate under stirring conditions, heating to 90° C. and refluxing for 100 minutes, cooling to room temperature after the reaction is completed, filtering, washing with deionized water and ethanol, and drying at 60° C. for 22 hours to prepare reduced graphene oxide; The mass ratio of hydrazine hydrate to graphene oxide is 0.875:

1.

2. A method for preparing the graphene-based antistatic coating according to claim 1, characterized in that: The method comprises the following steps: uniformly mixing o-cresol epoxy resin, dicyclopentadiene phenol epoxy resin, linear bisphenol A phenol resin, γ-methacryloxypropyl trimethoxysilane, polyphenylene sulfide, cellulose acetate butyrate, modified nickel-iron waste residue, modified red mud and reduced graphene oxide, then melt-extruding to obtain extruded sheets, and finally grinding and pulverizing to prepare a graphene-based antistatic coating.

3. The method for preparing the graphene-based antistatic coating according to claim 2, characterized in that: The stirring and mixing temperature is 75-80°C and the stirring and mixing time is 5-8min; The melt extrusion temperature is 154-157°C; Grind and pulverize through a 350 mesh sieve.

Citation Information

Patent Citations

  • Polymer / graphene anti-static coating, preparation method and application thereof

    CN104449010A

  • Graphene-containing UV coating

    CN109233365A